Will Hope Change Early Adult Women's Views About Love - Mahmuda, Nafila; Desmita, Desmita; Ananda, Fiqih; Wei, Li; Tan, Ethan (Yayasan Minang Darussalam, 2025)
Early adulthood ranges from 20-40 years. One of the important developmental tasks for early adults is having intimate relationships, (papalia, d.e., old, s. w.,& feldman, 2008) That is why many adult women are often trapped in romantic relationships with men that will either end happily or end in misery depending on what hopes or expectations underlie and motivate women's relationships in the early adult stages. According to most women, love will fail if someone does not try to actively develop their entire personality until they reach a productive orientation: that the fulfillment of one's love cannot be achieved without the ability to love other people, without humility and determination, as well as confidence and discipline. While adult women believe that love is just a matter of luck, something that will come if someone is lucky, but that does not mean that adults think love is not important. Hungry for it, women entering adulthood often watch films and read countless stories about the romantic love of couples. Both those that will have a happy ending and those that will have a tragic ending. That's the reason why researchers studied whether hope changes the way adult women view love.